Mahatma Gandhis Doctorian Of Ahimsa (International Journal of Food and Nutritional Sciences, 2022)
This study generally aimed to analyze Mahatma Gandhis doctrine of ahimsa. This paper employed the qualitative philosophical methods of research in analyzing the tenets of ahimsa in the representative literary work chosen. Ahimsa refers to the principle of nonviolence based on the sacredness of all living creatures and an important tenet of ancient Indian religious specifically Jainism Buddhism and Hinduism. Gandhi is one of the writer thinkers who philosophizes that ahimsa is the ontological core of existence . The salient points of the doctrine find their noblest expressions and exemplifications his life and works. While leading nationwide campaigns to ease the humanitarian issues of poverty women rights religious and ethnic harmony and injustices of the cast4r syst3em which are quite evident in his works Gandhi applied the principles on nonviolent civil disobedience playing a key role in freeing India from foreign domination